Bibliometric Study of Adaptive Rice (Oryza Sativa) Varieties and Adaptation Strategies Towards Extreme Climate - Mukhlis; Darmadi Erwin Harahap; Muhammad Darwis; Nikmah Sari Hasibuan; Nanda (Jurnal Penelitian Pendidikan IPA, 2025)
Extreme climate change poses a serious threat to global food security, particularly for rice, which is widely cultivated in tropical regions. Research on adaptive rice varieties and adaptation strategies is becoming increasingly important in responding to this challenge. This study aims to map developments, thematic trends, key actors, and collaborations in research on adaptive rice varieties to climate change, using a bibliometric approach. Data were obtained from the Scopus database for the period 2015–2025 using keywords related to “rice” and “climate adaptation/resilience.” The analysis was conducted using VOSviewer software for three main types of analysis: co-authorship, co-occurrence of keywords, and citation analysis. It was found that publications in this field continue to increase, with the largest contributions coming from China, India, and the United States. Dominant topics include climate-smart agriculture, genetic regulation, and biodiversity. The most prolific authors are Jat M.L., Hasegawa T., and Pan G. Citation analysis indicates a limited amount of highly influential literature, while collaboration networks between countries remain fragmented. The results of this study provide a comprehensive overview of the scientific landscape of adaptive rice research and climate strategies. These findings can be used to strengthen global collaboration, guide future research agendas, and support sustainable agricultural adaptation policies.